From Fighting for Women’s Rights to Fighting for Social Justice (Hana Gregorová: Ženy [Women] 1912, 1946) - Dana Hučková (Slovenska Literatura, 2022)
Hana Gregorová’s (1885 – 1958) early work was mostly concerned with themes pertaining to women’s emancipation. Later, the author widened her scope and also dealt with the questions of social justice. Feminist instrumentalisation as outlined in her debut collection of short prose Ženy ([Women] 1912) was combined with projecting a new, better world for all the impoverished ones. Social and pedagogical (didactic) function remained a stable characteristic of her writing. As to her themes, Gregorová was mainly concerned with the depiction of the suffering women and her empathising authorial narrator was a representative figure voicing progressive ideas. Works that the author published before 1918 (but also those from the first half of the 1920s) were later significantly revised. Gregorová updated her early work in accordance with the way her opinions evolved (especially with regards to her affinity towards socialist and communist ideas) and also as a reaction to the changes in social circumstances (the end of Second World War). Analysis of the revisions the author made in the second publication of the collection Ženy (1946) had a direct impact on the poetics of the texts and in turn also influenced the literary-historical reception of the collection – a fact that is most visible in cases in which the scholars only worked with the second edition.